Increasing Customer Live Streaming Engagement in Online Shopping Platforms - Hartono, Phebie Carissa; Priyana, Cynthia Susanty; Levia, Marleen; Simanjuntak, Evi Rinawati (Universitas Mercu Buana, 2023)
Nowadays, small business entrepreneurs use a new marketing tool to promote their products. This tool is named Live streaming.Objectives: This study aims to help online shop owners maintain customer live-streaming engagement so it can enhance viewers' participation through live-streaming commerce.Methodology: This study used quantitative data, utilizing a survey methodology and employing Indonesian citizens as the research's object. Respondents were obtained through Google form with 225 respondents to be analyzed using PLS-SEM. Variables were measured using a Likert scale. Finding: The result of this study suggests that interactivity, informativeness, and personalization correlate with customer engagement in live-streaming commerce.Conclusion: This research shows how to make a live streaming engagement using e-commerce which was influenced by interactivity, a response to an interaction between subscribers and streamers during live streaming. In addition, there is also informativeness that affects customer live-streaming engagement which is seen from the information provided by the streamer to customers. There is personalization which also affects live-streaming commerce. Future studies can be done in other countries by using the enormous shopping platform in their country with specific shopping platforms, specific sectors (fashion, electronics, food, and others), and measure customer live-streaming engagement using attractiveness because not many papers discuss this topic in Indonesia. Future studies also can distribute more questionnaires for more relevant and valid results and also add more factors like the increase in customer engagement in purchase intention or value co-creation.